Santa Claus is comin' to town [videorecording (DVD)] - Rankin, Arthur, Jr; Rankin, Arthur, Jr; Bass, Jules; Bass, Jules; Astaire, Fred; Rooney, Mickey; Wynn, Keenan, 1916-1986 (Original Christmas classic., 2010)
Where does Santa's suit come from? Why does he slide down the chimney? Why does he live at the North Pole? The answers to all these questions and the origins of our favorite holiday traditions are revealed in this classic about Kris Kringle, the world's most famous gift-giver.